2017
DOI: 10.12968/jowc.2017.26.sup9.s27
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence and incidence of diabetic foot ulcers among five countries in the Arab world: a systematic review

Abstract: The mean prevalence rates of DFU were highest in Saudi Arabia and Bahrain and lowest in Iraq. Saudi Arabia had the only reported incidence study, thus findings could not be compared to other countries of the Arab world. There were no studies identified during our search reporting prevalence rates of DFU in 17 of the 22 Arab countries. It is clear that further research is required to determine the incidence and prevalance of DFUs in the Arab world and that progress is needed in order to improve the quality of r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
24
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 22 publications
3
24
0
Order By: Relevance
“…A systematic review in six Arab countries showed that the mean prevalence of DFU was 6% (15). Thus, the frequency of DFU in the current study was higher than the DFU prevalence in the world, Asia, and the Arab world (7,15). However, some studies in line with our study had reported a higher frequency of DFU.…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…A systematic review in six Arab countries showed that the mean prevalence of DFU was 6% (15). Thus, the frequency of DFU in the current study was higher than the DFU prevalence in the world, Asia, and the Arab world (7,15). However, some studies in line with our study had reported a higher frequency of DFU.…”
Section: Discussionsupporting
confidence: 57%
“…A meta-analysis in 2017 showed that the DFU prevalence is 6.3% in the world and 5.5% in Asia (7). A systematic review in six Arab countries showed that the mean prevalence of DFU was 6% (15). Thus, the frequency of DFU in the current study was higher than the DFU prevalence in the world, Asia, and the Arab world (7,15).…”
Section: Discussionmentioning
confidence: 47%
“…Mauro Rigato reported the characteristics of patients with diabetic foot in Africa, with great attention to prevalence, amputation, and mortality of ulcers . Mairghani M et al also performed a systematic review to reveal prevalence and incidence of diabetic foot ulcers in the Arab world . However, the recurrence of diabetic foot has been neglected.…”
Section: Introductionmentioning
confidence: 99%
“…16 Mairghani M et al also performed a systematic review to reveal prevalence and incidence of diabetic foot ulcers in the Arab world. 17 However, the recurrence of diabetic foot has been neglected. Although recurrence rates of diabetic foot ulcers have been described in several published studies, they varied widely in different studies, and the sample sizes of those studies were small.…”
mentioning
confidence: 99%
“…However, only a few studies have investigated these DFU markers in Arab countries. A recent systematic review identified nine papers from five countries with varying DFU prevalence rates of between 2.7% in Iraq and 11.85% in Saudi Arabia [20]. One paper from Saudi Arabia reported an incidence rate of 1.8% [21].…”
Section: Introductionmentioning
confidence: 99%